Energy-efficient Conversion of Microalgae to Hydrogen and Power. (May 2017) - Aziz, Muhammad; Zaini, Ilman Nuran
Abstract: An integrated system for H2 production from microalgae and its storage is proposed employing enhanced process integration technology (EPI). EPI consists of two core technologies, i.e. exergy recovery and process integration. The proposed system includes a supercritical water gasification, H2 separation, hydrogenation, and combined cycle. Microalga Chlorella vulgaris is used as a material for evaluation. The produced syngas is separated to produce highly pure H2 . Furthermore, to store the produced H2, liquid organic H2 carrier of toluene-and-methylcyclohexane cycle is adopted. The remaining gas is used as fuel for combustion in combined cycle to generate electricity. The effects of fluidization velocity and gasification pressure to energy efficiency are evaluated. From process modeling and calculation, it is shown that high total energy efficiency, about 60%, can be achieved. In addition, about 40% of electricity generation efficiency can be realized.